Synthesis and molecular docking of carvone derivatives as a potential neuraminidase inhibitors - Jusoh, Noorakmar; Abd Hamid, Shafida; Muhamad Bunnori, Noraslinda (2016)
Recent outbreaks of highly pathogenic and occasional drug-resistant influenza strains have highlighted the need to develop novel anti-influenza therapeutics. Here, we design, synthesized, and report computational analysis of carvone derivatives as potential neuraminidase inhibitors. A series of carvone derivatives were synthesized by following a four-step strategies. All isolated compounds obtained were elucidated using 1H NMR, 13C NMR, and CHNS analysis. Docking studies were performed using AutoDock 3.0.5 to study the interactions of the neuraminidase (NA) with the ligands. Based on docking analysis, compound 3 was found to interact better in NA active site compared other compounds with the lowest free energy binding of -7.39 kcal/mol.